POLICE APPARATUS ROLE IN DETERMINING THE PERPETRATORS’ RESPONSIBILITY FOR DESTRUCTION OF GOODS CONDUCTED BY COMMUNITY (IN CASE OF TRAFFIC ACCIDENTS IN KAUR) - Rianto Ade Putra; Antory Royan Adyan; Hamzah Hatrik (Bengkoelen Justice : Jurnal Ilmu Hukum, 2021)
On Sunday of August 2nd, 2015 in Tanjung Harapan highway, Semidang Gumay District of Kaur Regency there has been a vigilantism (Eigenrichting) in the form of destruction and burning of one (1) unit of car that carried out jointly by the community, but until the study was conducted, there has been no follow-up for perpetrators of the destruction and burning of the car, so it raises the question whether the actions taken by community in Tanjung Harapan Village cannot be prosecuted. The purpose of this study was to determine how the role of Police Apparatus in determining the responsibility of perpetrators for destruction and burning of the car. The results showed that the role of Police in determining the responsibility of perpetrators for destruction of goods conducted by community was as the investigators in that case, and must make a report of criminal acts as referred to Article 6 Paragraph (1) and Paragraph (2) of   Head of the Indonesian Police (PERKAP) Number 12 of 2009, then these reports provide a basis for investigation in accordance with the provisions laid down in the Criminal Code. Police as investigators may use Article 406 Paragraph (1) and Article 170 of the Criminal Code as a chapter of suspicion in the investigation process against the destruction of goods conducted jointly by the members of the community in Tanjung Harapan Village of Kaur Regency.